Pengaruh Iklim Organisasi, Etos Kerja dan Disiplin Kerja terhadap Efektivitas Kinerja Pegawai Lembaga Pemasyarakatan Kelas IIA Lhokseumawe - Ardi Isriansyah, Aulia; Luthfi, Luthfi; Iskandar, Raihan (Aceh Cooperative Care, 2024)
Research was conducted on employees of the Lhokseumawe Penitentiary, to examine the contribution of performance effectiveness related to organizational climate factors, work ethic and work discipline. It is a research survey, quantitative with an associative type. Based on the path model analysis between variables, it was found; (1) organizational climate factors, work ethic and work discipline are causally interconnected. (2) the contribution of the three significant factors to the effectiveness of employee performance, with a direct and indirect influence on organizational climate of 48.99%, the work ethic factor of 55.88% and the influence of work discipline of 54.31%. (2) Simultaneously, organizational climate, work ethic and work discipline have real implications for the performance of prison employees with contributions 42,2%.